Sugar, Spice, and the Not So Nice Comics Picturing Girlhood - Pursall, Dona; Van de Wiele, Eva (Studies in European Comics and Graphic Novels, 2023)
Girls, gender and identity in comicsSugar, Spice, and the Not So Nice offers an innovative, wide-ranging and geographically diverse book-length treatment of girlhood in comics. The various contributing authors and artists provide novel insights into established themes within comics studies, children's comics, graphic medicine and comics by and about refugees and marginalised ethnic or cultural groups. The book enriches traditional historical, narratological and aesthetic approaches to studying girlhood in comics with practice-based research, discussion and conversation. This re-examination of girls, gender and identity in comics connects with contemporary discourse on gender identity politics. Through examples from both within Europe, the anglophone world and beyond, and including visual essays alongside critical theory, the volume furthermore engages with new developments in contemporary comics scholarship. It will therefore appeal to students and scholars of childhood studies, comics scholars and creators, and those interested in addressing gender identity through the prism of comics. Contributors: Mel Gibson (Northumbria University), Martha Newbigging (Seneca College), María Porras Sánchez (Complutense University of Madrid), JoAnn Purcell (York University and Seneca College), Benoît Glaude (Ghent University/University of Louvain), Sylvain Lesage (University of Lille), Joan Ormrod (Manchester Metropolitan University), Aswathy Senan (The Research Collective Delhi), Michel De Dobbeleer (Ghent University), Sébastien Conard (KASK Ghent School of Arts and LUCA Brussels), Marthine Bertiot (University of Edinburgh), Julia Round (Bournemouth University) Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).